Individuals with reactive arthritis suffer from poor health-related quality of life akin to individuals with ankylosing spondylitis: A multigroup study - Prakash Gupta; Rajat Kharbanda; Maryam Abbasi; Roma Raj; Latika Gupta (Indian Journal of Rheumatology)
Background: Reactive arthritis (ReA) and ankylosing spondylitis (AS), both spondyloarthropathies predominantly affecting young men seriously hamper mobility during the active phases of disease. While AS is thoroughly researched, specific studies on ReA are relatively scarce despite its pervasive nature and ever evolving epidemiology. Thus, it is imperative to understand the quality of life (QoL) of ReA patients in comparison to those with AS and healthy controls (HC) to reduce the disparity in patient care. Methods: An inception cohort of adults with ReA (Braun’s criteria) was surveyed to collect the data on demographics, clinical profile, disease activity (Bath AS Disease Activity Index [BASDAI], pain Visual Analog Scale [VAS]), functional status Bath AS Functional Index (BASFI), and QoL (ASQoL instrument) between November 2019 and January 2020. HC and AS were surveyed for the same parameters using an anonymized e-survey (SurveyMonkey.com). All the data are expressed as medians and interquartile range. Results: A total of 147 participants (62 ReA, 45 AS and 40 HC) were included. Patients with ReA were younger than those with AS and HC - 25, 29, and 28 years, respectively, and had a shorter disease duration (P < 0.0001). Baseline clinical characteristics (peripheral arthritis and enthesitis), pain VAS (body pain and back pain) were comparable in ReA and AS groups. All the clinical characteristics of ReA and AS cohorts were significant in comparison to the HC cohort. Notably, functional and activity scores of AS and ReA patients were similar, whereas all functional scores of patients with either spondyloarthropathy were significantly worse than HC (BASDAI, BASFI, ASQoL, P < 0.0001). ASQoL scores were comparable across all domains of ReA and AS except in upper limb activities where patients with ReA fared better than AS. No difference in QoL was observed between acute or chronic ReA. Conclusion: QoL in ReA and AS is comparable, thus the impact of disease on physical function must be recognized to improve patient care. Patients with ReA exhibit significantly worse QoL than HC using ASQoL instrument.